Validation of the Spanish version of the Pediatric Symptom Checklist (PSC) to identify and assess psychosocial problems among early adolescents in Chile - Ramírez Saray; Gana Sofia; Godoy Maria I; Valenzuela Daniela; Araya Ricardo; Gaete Jorge (Public Library of Science, 2025)
Background
The high prevalence of mental disorders in early adolescents, and their consequences, encourage the need for validated instruments to identify and assess psychosocial problems.
Objectives
i) To evaluate the psychometric properties of the Spanish version of the Pediatric Symptom Checklist (PSC) questionnaires (PSC-Y, 35 items, and PSC-17-Y) and its subscales (Attention, Internalizing and Externalizing subscales), including the assessment of the item structure, concurrent validity, and reliability; and ii) To assess possible associations between bullying experiences, school climate and school membership with psychological problems identified by the PSC questionnaire.
Methods
A cross-sectional study was carried out in 39 schools in Santiago, Chile. The sample consisted of 3,968 adolescents aged between 10 and 11 years. A descriptive analysis of the Pediatric Symptom Checklist was performed along with measures of dimensionality, reliability, and correlations with a validated questionnaire exploring similar constructs, the Strengths and Difficulties Questionnaire. Finally, associations of bullying, school climate, and school membership with the three subscales of the PSC were explored.
Results
Both versions of PSC had problems with item #7 (Act as if driven by motor), which did not load in any of the latent factors. It was removed from later analyses. The three-factor structure of PSC was confirmed. All remaining items had high factor loadings in their corresponded latent factors, and the reliability was high for the total scales (PSC-34-Y, ω = 0.78; PSC-16-Y, ω = 0.94) and the subscales of PSC-16-Y (Attention, ω = 0.77; Internalizing, ω = 0.79; Externalizing, ω = 0.78). The goodness of fit was adequate, and the correlation between PSC subscales and SDQ subscales was high. Victimization and perpetration were associated with all PSC subscales, and higher school climate and stronger school memberships were negatively associated with PSC symptoms.
Conclusions
The current findings seem to demonstrate that the Spanish version of the PSC is a valid and reliable instrument for identifying and assessing psychosocial problems in early adolescents.